Smoki, błyski i pochodnie jako kluczowe elementy literackiej wizji schyłku w twórczości porozbiorowej Jana Pawła Woronicza - Martyna Ujma (Zagadnienia Rodzajów Literackich)
The subject of analysis and interpretation in the article Dragons, flashes and torches as elements of the literary vision of decline in Jan Paweł Woronicz’s the post-partition works is Jan Paweł Woronicz’s writings (poetry, sermons and homilies), who lived from 1757–1829. Through the careful observation of the language used in Woronicz’s works, the author tries to extract metaphors which show a sense of apathy and decline at the turn of the century. The author also attempts to reach the substructure of the preacher-poet’s thinking and to make a critical reflection on the state of culture in a specific period of time — namely the last years of the 18th century and the first decades of the 19th century. She treats metaphors not only as stylistic means, but also as visible signs (phenomena) of feelings towards the world, and recognizes at the same time that Woronicz’s work is one of many testimonies to the intensified intellectual and cultural movement of Poland at the turn of the 18th and 19th centuries. In the article, the author presents Woronicz as a representative of time “in between,” and as an individual who has experienced something new, an often difficult situation that occurred within the framework of intense changes to the political and aesthetic paradigm that took place at the turn of the centuries.